Income variability, evolving diets, and elasticity estimation of demand for processed foods in Nigeria - de Brauw, Alan; Herskowitz, Sylvan (Agricultural and Applied Economics Association, 2021)
We present evidence on evolving dietary patterns in Nigeria using six rounds of household consumption data from the Nigerian General Household Survey panel between 2011 and 2016. First, following conventional definitions in the literature, we show that Nigeria has not shown any aggregate increase in consumption of highly processed foods over this period, contrary to patterns observed elsewhere in the region. In fact, consumption of highly processed foods at home has declined, while food consumed away from home, often assumed to be highly processed, has risen substantially. We then show that estimates of food expenditure elasticities of different food types are highly sensitive to different estimation approaches and raise concerns about some frequently used methods in the literature. In the absence of credible exogenous variation, we argue for the importance of panel methods and household fixed effects to control for time invariant factors likely to confound cross‐sectional estimates. Finally, we examine semiparametric Engel curves for different food groups and find that apparent curvature in the relationships between food budget shares and overall food expenditure levels in the raw data become nearly linear when removing variation explained by time‐invariant household factors.